1988
DOI: 10.1007/bf00322449
|View full text |Cite
|
Sign up to set email alerts
|

Two alleles of the single-copy chalcone synthase gene in parsley differ by a transposon-like element

Abstract: Two types of genomic DNA hybridizing with a chalcone synthase cDNA were isolated from cell suspension cultures of parsley (Petroselinum crispum cv. Mooskrause) and cloned in lambda EMBL4. Their fragmentation patterns with several common restriction enzymes were identical, except for the occurrence of a 927 base pair insertion in one type relative to the other. This insertion is located 538 base pairs upstream of the first of two transcription start sites and has characteristic features of a transposable elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…Significant methylation of nonsymmetrical cytosines was also observed in an endogenously duplicated, partially silenced copy of the maize R gene (Ronchi et al, 1995). a Maize Ac (Kunze and Starlinger, 1989); Japanese morning glory Tpnl (Hoshino et al, 1995); soybean Tgml (Rhodes and Vodkin, 1988); parsley Tpc7 (Herrmann et al, 1988); maize EnLSpm (Gierl et al, 1988); Arabidopsis Tatl (Peleman et al, 1991); snapdragon Tam3 (Hehl et al, 1991). b Number of repeats at both ends of the transposon.…”
Section: Methylation Of Nonsymmetrical Cytosine Residuesmentioning
confidence: 99%
“…Significant methylation of nonsymmetrical cytosines was also observed in an endogenously duplicated, partially silenced copy of the maize R gene (Ronchi et al, 1995). a Maize Ac (Kunze and Starlinger, 1989); Japanese morning glory Tpnl (Hoshino et al, 1995); soybean Tgml (Rhodes and Vodkin, 1988); parsley Tpc7 (Herrmann et al, 1988); maize EnLSpm (Gierl et al, 1988); Arabidopsis Tatl (Peleman et al, 1991); snapdragon Tam3 (Hehl et al, 1991). b Number of repeats at both ends of the transposon.…”
Section: Methylation Of Nonsymmetrical Cytosine Residuesmentioning
confidence: 99%
“…See Schulze-Lefert et al (1 989) for footprint data not included in Figure 2, and for the details of the original construction from which all new promoter mutants are derived. Note that the CHS" promoter was previously referred to as the CHS-1 promoter (Herrmann, 1987;Herrmann, Schulz, and Hahlbrock, 1988;Schulze-Lefert et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…either of the two CHS promoter alleles that occur in parsley (constructs 041 and O1 1). They are sequence identical to position -584 (Herrmann, 1987;Herrmann, Schulz, and Hahlbrock, 1988). Comparison of light-activated GUS expression revealed that the 615-bp promoter is, if anything, slightly more light-responsive than a promoter of 2.0 kb.…”
Section: Silent Far Upstream Light-responsive System(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the 5'-flanking sequences of cyp73a and cyp73b contain many boxes that are conserved among the promoters of several genes involved in phenylpropanoid biosynthesis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] These boxes ( Fig. 2A) have been shown to display elicitor-inducible "footprints" in vivo, and to be related to expression in flowers!…”
Section: Characterization Of Aspen Ca4h Homologous Genesmentioning
confidence: 99%